A escuta diferenciada das dificuldades de aprendizagem: um pensarsentiragir integral mediado pela musicoterapia - NASCIMENTO, Sandra Rocha do (2010)
The project, developed at the line of research Culture and Educacional Process, analise the difficulty of learning (DA) on a full time school with the objective to understand its expression and action proposition. The methodology based on a whole search action, at perspective existence phenomenon using lots of techniques, data collection and actions music therapy interdisciplinary multidirectional to support on listening, balancing experiences, actions and comprehension. The results point to theree axial categories: life space interinfluent, intersubjective perception and acts interflectives, showing that DA must be seem to the point of differential and amplification, configurate music therapy as time- space of trans-formation to dimensions for think, feel and act. The referential theory and subsidiary of Merleau-Ponty, on her proposal analytical hyper dialectic the proposition of the dialog with other theory. Same as a real complex, a DA and multifactor‟s interinfluent are explained by different approaches, across study on education areas psychology and music therapy (LEWIN, 1965;1973; FREIRE, 1970; RIBEIRO, 1994; BARCELLOS, 2004). Learning difficulties were understood in a broad way, through a differentiated listening that integrated (knowledge and locus varied in their speeches) to the apprehension of the mutual constitution of subject and medium. Understanding this fully, depending on the category-selective -thinkfeelact- leading to a shift of focus on the phenomena, in which LEARNING disabilities are presented as a disSONANCE BETWEEN THINKFEELACT.